Enhancing Regional Trade Integration in Southeast Europe - Handjiski, Borko (World Bank, 2012)
Countries of the Southeast Europe (SEE) region have witnessed significant economic improvement since the beginning of their transition to market economies in the early 1990s. Growth has been particularly strong in the past six years, but still lower than in other fast growing countries in the East Asia and Baltic regions, or some of the other new member states of the European Union (EU). The purpose of this study is twofold: (i) to present recent trends in intra regional trade in SEE, in particular following the implementation of Central European Free Trade Agreement (CEFTA); and (ii) to bring the attention of policy makers to some of the remaining impediments to enhanced intra regional trade. The rest of the study is organized as follows. Chapter two describes intraregional trade patterns, both prior and after the entry of CEFTA into force, including more detailed analysis of trade structure. Chapter three emphasizes the role of nontariff barriers (NTBs), such as technical regulations and standards, and their potential impact on trade enhancement, as well as the importance of the trade related environment drawing on global surveys and reports (doing business, Business Environment and Enterprise Performance Survey (BEEPS), logistics performance indicator, and the enabling trade index). It also looks at rules of origin and their role in trade creation. Chapter four aims to present the view of the private sector on CEFTA and on trade related reforms in general through two case studies of regional firms. Finally, chapter five concludes by summarizing the key recommendations of the study.